Challenges of Affective Assessment of Islamic Religious Education Learning in Merdeka Curriculum - Susmiyati, Sri; Zurqoni, Zurqoni; Abdillah, Muhamad Hasan; Saugi, Wildan (Al-Hayat: Journal of Islamic Education, 2023)
This study aims to identify the challenges of madrasah teachers in the affective assessment of Islamic Religious Education based on the Independent Curriculum and to evaluate the understanding and abilities of teachers. This study uses a mixed explanatory method, with a quantitative method through a survey of 177 Islamic Religious Education teachers in East Kalimantan selected through simple random sampling from 378 teachers. Qualitative data were collected through interviews and observations. Quantitative analysis uses descriptive statistics (SPSS-25.0), and qualitative analysis uses the interactive model of Miles, Huberman, and Saldana. This study reveals that the main challenges in affective assessment for Islamic Religious Education (PAI) teachers based on the Independent Curriculum include: (1) teachers' lack of understanding of religious affective assessment, (2) limited ability to carry out assessments, (3) low skills in using affective assessment methods and instruments, and (4) minimal support in terms of training, resources, and time. Teachers tend to focus more on cognitive assessments, causing students' affective assessments of religiosity to be less monitored. The implications of this study emphasize the importance of improving teacher competence in understanding and assessment skills, as well as training and resource support. Future research should develop an effective assessment training model based on the Merdeka Curriculum, including practical instruments, technology support, and collaboration between schools, government, and related parties to strengthen teacher capacity.